Studies of Si-Fe-C Electrode Materials Prepared by Combinatorial Sputter Deposition. Issue 2 (1st January 2017) - Al-Maghrabi, M. A.; Chevrier, V. L.; Dahn, J. R.; Sanderson, R. J.; Dunlap, R. A.
Abstract : Four libraries of the Si-Fe-C system were produced using combinatorial sputtering methods. X-ray diffraction was used to study the structure of the thin films and showed that all portions of the films were amorphous or nanostructured. Room temperature 57 Fe Mössbauer spectroscopy was utilized to study the atomic environment around the Fe atoms. Cyclic voltammetry measurements were performed to study the behavior of these materials as negative electrodes for Li-ion batteries. Through a combined consideration of Mössbauer effect measurements and electrochemical data, it is suggested that the alloys are a combination of Si-Fe and Si-C phases and active Si and C nanometer-scale grains. Some of these electrodes (for example, Si66 Fe16 C18 ) show initial specific reversible capacities of near 1500 mAh/g and specific capacities of near 1200 mAh/g after 25 cycles.